Physical activity levels and functional fitness in older adults in the Alentejo region, Portugal - Bravo, Jorge (2019)
Objective: This study aims to study the relationship between physical activity levels, mea- sured with accelerometry, and functional fitness in older adults in the Alentejo region, Portugal. Methods: Fifty-five men and 100 women, aged 65 years and over, were evaluated for the intensity of daily physical activity with accelerometers and for functional fitness with the Senior Fitness Test battery. The associations between functional fitness and time spent in physical activity at different intensities were analyzed. Results: Negative associations were found between sedentary activity time and aerobic endurance, upper-body flexibility and agility. On the other hand, mild and moderate phys- ical activity time showed a positive association with strength, upper-body flexibility, agili- ty and aerobic endurance, both on weekdays and on weekends. Similar results were found for the time spent in moderate physical activity. Conclusions: More active older adults exhibit better functional fitness. The results of this study reinforce the importance of promoting physical activity and reducing sedentary be- haviors to improve functional fitness and autonomy in the elderly.